Water-Dependent Reduction of Carbohydrate Azides by Dithiothreitol - Komarova, Bozhena S.; Maryasina, Sofia S.; Tsvetkov, Yury E.; Nifantiev, Nikolay E. (Synthesis, 2013)
Dithiothreitol efficiently reduces carbohydrate azides in aqueous acetonitrile to give good-to-excellent yields of the corresponding amines or, after N-acetylation, acetamides. This reduction can proceed in either the presence or the absence of a base.
Keywords: azides; carbohydrates; reductions; amines; amides